sin θ cos 7θ cos 4θ + sin 7θ cos θ cos 4θ + sin 4θ cos 7θ cos θ = sin θ sin 4θ sin 7 θ.
prove no spam
Answers
Answered by
1
Answer:
Hope it will help you
Step-by-step explanation:
1 – tan θ tan 4θ = 0, then given equation becomes
cos θ cos 4θ – sin θ sin 4θ = 0
or, (cos 3θ – cos 5θ) – (cos 5θ – cos 3θ) = 0 or,
2 (cos 3θ – cos 5θ) = 0
or, cos 3θ = cos 5θ
⇒ 5θ = 2nπ ± 3θ ……… (1) t
Taking positive sign of (1) or, 2θ = 2nπ
or, θ = nπ, where n = 0, ±1, ±2 ………
Taking negative sign of (1) or, 8θ = 2nπ
or, θ = nπ/4 where n = 0, ±1, ±2 ………
Check
Put θ = nπ in given equation 0 = 0
Put θ = nπ/4 in given equation 1/√2.1/√2 (-1) + (1/√2)(1/√2)(-1) + 0 = 0
So θ = nπ and nπ/4. Also satisfy given equation θ = nπ, nπ/4, nπ/12, where n = 0, ±1, ±2 ………
Answered by
0
Answer:
djsbdbsmwnsnnsnsnwnnsnsb
Similar questions
Math,
3 months ago
Chemistry,
3 months ago
History,
3 months ago
Environmental Sciences,
7 months ago